Crystal structure of (E)-N′-{[(1R, 3R)-3-isopropyl-1-methyl-2-oxocyclopentyl]methylidene}-4-methylbenzenesulfonohydrazide. (February 2015) - Tymann, David; Dragon, Dina Christina; Golz, Christopher; Preut, Hans; Strohmann, Carsten; Hiersemann, Martin
No abstract available